UJI AKTIVITAS EKSTRAK DAN FRAKSINASI DAUN BRUCEA JAVANICA (Merril) SECARA INVITRO - Megawati Megawati; M Angelina (Research Center for Chemistry - LIPI, 2010)
Brucea javanica (Merril) is a tropical plant widely grown in Indonesia, Brucea javanica has a bitter taste efficacious to reduce the heat and remove toxins, lethal parasites, anti-anti-dysentery and malaria. Chemical compounds contained in many of which have bioactivity. Antidiabetic test has been performed with a-glucosidase method, anti-oxidant test method